Comparison of Intravitreal Aflibercept and Ranibizumab following Initial Treatment with Ranibizumab in Persistent Diabetic Macular Edema - Ali Demircan; Zeynep Alkin; Ceren Yesilkaya; Gokhan Demir; Burcu Kemer (Journal of Ophthalmology)
Purpose. To compare the visual and anatomic outcomes in patients with persistent diabetic macular edema (DME) who switched from ranibizumab to aflibercept with those who continued with previous ranibizumab therapy. Methods. In this retrospective comparative study, medical records of consecutive patients with center-involved DME ≥ 350 μm who had at least three recent consecutive monthly ranibizumab injections followed by as-needed therapy with either aflibercept or ranibizumab were reviewed. Data were collected at presentation (preinjection), at the intermediary visit, and at the last visit (at the end of the follow-up period). Results. Forty-three eyes of 43 patients were divided into two groups: the switch group (n=20) and the ranibizumab group (n=23). Though no significant improvement was found in the mean BCVA from the intermediary visit to the last visit, there was a difference in the mean CMT in the switch group and the ranibizumab group (p<0.001 and p=0.03, resp.). The mean CMT decreased after the intermediary visit by 188.6 ± 120.5 μm in the switch group and by 60.3 ± 117.1 μm in the ranibizumab group (p=0.003). Conclusions. Both aflibercept and ranibizumab decreased CMT in patients with persistent DME who showed a poor response to ranibizumab injections. However, switching to aflibercept provided only morphologic improvement.